More than one way to free choice: A view from child Romanian - Bleotu, Adina Camelia; Panaitescu, Mara; Cremers, Alexandre; Nicolae, Andreea; Benz, Anton; Bîlbîie, Gabriela; Tieu, Lyn (Proceedings of the Amsterdam Colloquium, 2024)
Studies show that children draw from modalized disjunctive statements of the structure X is allowed to do P or Q (♢(P ∨Q)) a Free Choice (FC) inference, namely X is allowed to do P and X is allowed to do Q (♢P ∧♢Q). Their ability to compute free choice inferences is surprising in light of their well-known difficulties with scalar implicatures involving non modalized disjunction (Tieu, Romoli, et al. 2016), particularly on accounts that unify free choice inferences and scalar implicatures (e.g., Kratzer and Shimoyama 2002; Chierchia 2013). Recent work by Cochard, van Hout, and Demirdache (2024b), however, argues that some children only seemingly derive free choice: these children actually interpret ♢(P ∨Q) as ♢(P ∧Q), which follows from their conjunctive understanding of non-modalized disjunction. In the present study, we extend the investigation by comparing the same children’s performance on non-modalized and modalized utterances in Romanian, an understudied language. Specifically, we tested the same group of 5-year-old monolingual Romanian-speaking children and adult controls, balanced for order. Our findings provide partial evidence for Cochard, van Hout, and Demirdache (2024b)’s hypothesis: some children were inclusive with non-modalized disjunction, and appeared to derive genuine free choice on the free choice task, while some children indeed exhibited conjunctive interpretations in both tasks.